Linguistic Shifts: A Relatively Effortless Route to Emotion Regulation?. (December 2019) - Orvell, Ariana; Ayduk, Özlem; Moser, Jason S.; Gelman, Susan A.; Kross, Ethan
Prior research indicates that psychological distance facilitates emotion regulation. Here, we propose that the ability to transcend one's immersed perspective may be hidden in plain sight, within the very structure of language. We review evidence regarding two linguistic mechanisms, distanced self-talk and generic "you, " that promote emotion regulation by allowing speakers to shift from an immersed to a more distanced perspective through the words they use to reflect on the self (e.g., shifting from "I" to their own name or other non-first-person-singular pronouns). We conclude by suggesting that these linguistic shifts occur relatively seamlessly and thus may provide a less effortful route to emotion regulation.